Induced pluripotent stem cells from human hair follicle keratinocytes as a potential source for in vitro hair follicle cloning - Lim, Sheng Jye; Ho, Shu Cheow; Mok, Pooi Ling; Tan, Kian Lee; Ong, Alan Han Kiat; Gan, Seng Chiew (PeerJ, 2016)
Background: Human hair follicles are important for the renewal of new hairs and their development. The generation of induced pluripotent stem cells (iPSCs) from hair follicles is easy due to its accessibility and availability. The pluripotent cells derived from hair follicles not only have a higher tendency to re-differentiate into hair follicles, but are also more suited for growth in hair scalp tissue microenvironment. Methods: In this study, human hair follicular keratinocytes were used to generate iPSCs, which were then further differentiated in vitro into keratinocytes. The derived iPSCs were characterised by using immunofluorescence staining, flow cytometry, and reverse-transcription PCR to check for its pluripotency markers expression. Results: The iPSC clones expressed pluripotency markers such as TRA-1-60, TRA-1-81, SSEA4, OCT4, SOX2, NANOG, LEFTY, and GABRB. The well-formed three germ layers were observed during differentiation using iPSCs derived from hair follicles. The successful formation of keratioctyes from iPSCs was confirmed by the expression of cytokeratin 14 marker.Discussion: Hair follicles represent a valuable keratinocytes source for in vitro hair cloning for use in treating hair balding or grafting in burn patients. Our significant findings in this report proved that hair follicles could be used to produce pluripotent stem cells and suggested that the genetic and micro-environmental elements of hair follicles might trigger higher and more efficient hair follicles re-differentiation.